Metabolomics of Escherichia coli Treated with the Antimicrobial Carbon Monoxide-Releasing Molecule CORM-3 Reveals Tricarboxylic Acid Cycle as Major Target - Carvalho, Sandra M. (2020)
In the last decade, carbon monoxide-releasing molecules (CORMs) have been shown to act against several pathogens and to be promising antimicrobials. However, the understanding of the mode of action and reactivity of these compounds on bacterial cells is still deficient. In this work, we used a metabolomics approach to probe the toxicity of the ruthenium(II) complex Ru(CO)3Cl(glycinate) (CORM-3) on Escherichia coli. By resorting to 1H nuclear magnetic resonance, mass spectrometry, and enzymatic activities, we show that CORM-3-treated E. coli accumulates larger amounts of glycolytic intermediates, independently of the oxygen growth conditions. The work provides several evidences that CORM-3 inhibits glutamate synthesis and the iron-sulfur enzymes of the tricarboxylic acid (TCA) cycle and that the glycolysis pathway is triggered in order to establish an energy and redox homeostasis balance. Accordingly, supplementation of the growth medium with fumarate, α-ketoglutarate, glutamate, and amino acids cancels the toxicity of CORM-3. Importantly, inhibition of the iron-sulfur enzymes glutamate synthase, aconitase, and fumarase is only observed for compounds that liberate carbon monoxide. Altogether, this work reveals that the antimicrobial action of CORM-3 results from intracellular glutamate deficiency and inhibition of nitrogen and TCA cycles.